La norma internacional de contabilidad nic 2 inventarios. Incidencia en la presentación razonable de los estados financieros de la empresa agro servicios cox del cantón el Empalme, periodo 2023 - Vélez Burgos, Boris Patrico (2025)
This research examines the application of IAS 2 Inventories in Agro Servicios Cox in the canton of El Empalme during the year 2023 and its effect on the fair presentation of financial statements. The study highlights inventories as a critical asset in the agricultural sector, whose proper management directly influences management decision making. The methodology used was a mixed approach: qualitative, through documentary research and interviews with personnel; and quantitative, analyzing data from the income statement. Inductive, deductive, analytical, synthetic and historical-logical methods were applied to evaluate accounting procedures and valuation methods. The results show that the company complies significantly with IAS 2, using the PEPS method and Net Realized Value to value